Uteh Bateh Traditional Kerinci Government in The Tambo Kerinci Manuscript - Fiadi, Agus; Aliyas, Aliyas; Zahara, Mina (Fakultas Ushuluddin, Adab dan Dakwah IAIN Kerinci, 2023)
This article explains the history of the Kerinci Traditional Government which is called Kemandapoan, where is the government system Kemendapoan This was created based on the Ordinance Law of 1918(StandsLeaf-No.677) be equipped withInlandche OrdinanceOuter regions (IGOB) September 3, 1938 (State plate No: 490) Jo Stb 1938 No 681) issued by the Dutch Colonial Government. Kemandapoan This has territorial boundaries which in the local language of the Kerinci people are known as Uteh Bateh which is very important to explain because it concerns the sovereignty of a Territory. The aim of this research is to find out the boundaries of traditional territories which have experienced shifts along with the continued development of a region with expansion, especially from the expansion of districts into regencies and municipalities as well as the many expansions of villages which will make it difficult to remember the boundaries of traditional government areas or Traditional Government. The method used in this research is a philological research method which includes determining the text; manuscript inventory; manuscript description; comparison of manuscript and text; text transliteration; as well as text translation. The results of this research are that the traditional government in Kerinci used to be 10 Kemendapoan. Kemendapoan this is at the same level as a sub-district, but now the administrative boundaries of the traditional territory include a sub-district, because there have been many changes, starting from the expansion of Kerinci Regency and Sungai Full City to the expansion of several villages. Mendapo emerged because of the will of the Kerinci Community and also the Dutch Colonial initiative which invited traditional leaders, both Depati, Ninik Mamak, Tengganai, Scholars of Ulama, Smart Clerks and youth (Hulubalang) to hold deliberations on the formation of a new government system. The aim of the formation of the Kemendapoan was for the Dutch to reduce leadership dominance Depati in their traditional territory which the Dutch feared would backfire on the Dutch position in the Kerinci region. Tulisan ini menjelaskan tentang sejarah Pemerintahan Tradisional Kerinci yang disebut dengan Kemandapoan, dimana sistem pemerintahan Kemendapoan ini dibuat berdasarkan undang undang ordonansi tahun 1918 (Staat Blaad-No.677) di lengkapi dengan Inlandche Ordonansi Buitenggewesten ( IGOB ) tanggal 3 September 1938 ( Staatblaad No:490) Jo Stb 1938 No 681) yang dikeluarkan oleh Pemerintahan Kolonial Belanda. Kemandapoan ini mempunyai batas Wilayah yang dalam bahasa lokal masyarakat Kerinci dikenal dengan istilah Uteh Bateh yang sangat penting dijelaskan karena menyangkut kedaulatan suatu Wilayah. . Adapun tujuan dari penelitian ini adalah untuk mengetahui batas wilayah adat yang telah mengalami pergeseran seiring dengan terusnya berkembang suatu wilayah dengan adanya pemekaran, mulia dari pemekaran Kabupaten menjadi Kabpaten dan Kota Madya juga banyaknya terjadi pemekaran Desa yang nantinya akan menyulitkan untuk mengingat batas wilayah pemerintahan Tradisonal/Pemerintahan Adat. Metode yang digunakan daam penelitian ini adalah metode penelitian filologi yang meliputi penentuan teks; inventarisasi naskah; deskripsi naskah; perbandingan naskah dan teks; transliterasi teks; serta terjemahan teks. Adapaun hasil dari penelitian ini adalah bahwa pemerintahan tradisional yang ada di Kerinci dahulunya adalah 10 Kemendapoan. Kemendapoan ini setingkat dengan kelurahan tapi sekarang batas administratif wilayah adat mencakup sebuah Kecamatan, karena telah banyak terjadi perubahan mulai dari Pemekaran Kabupaten Kerinci dan Kota Sungai Penuh sampai dengan pemekaran beberapa Desa. Mendapo muncul karena kehendak Masyarakat Kerinci dan juga inisiatif Kolonial Belanda yang mengajak Pemuka adat, baik Depati, Ninik Mamak, Tengganai, Alim Ulama, Cerdik Pandai dan pemuda (Hulubalang) untuk mengadakan musyawarah pembentukan suatu sistem pemerintahan baru. Pembentukan Kemendapoan ini bertujuan bagi Belanda untuk mengurangi dominasi kepemimpinan Depati di wilayah adatnya yang di takutkan Belanda akan menjadi bumerang bagi kedudukan Belanda dalam wilayah Kerinci.